Perceived Support, Job Opportunities, Work-Life Balance, and Turnover Intention: Study on Gen Z Employees at Kopi Kenangan - Faniatus Shalihah; Denis Fidita Karya (Universitas Dinamika, 2026)
Aims - This study aims to analyse the effect of Work-Life Balance (WLB) on Turnover Intention (TI) among Generation Z employees, specifically examining the moderating roles of Perceived Organisational Support (POS) as an internal factor and Perceived Job Opportunities (PJO) as an external factor. Methodology - This study utilises an explanatory quantitative research design. Data were collected via structured questionnaires using a 5-point Likert scale from a sample of 180 Generation Z employees (born between 1997–2012) working across Kopi Kenangan outlets in Surabaya, Indonesia. Hypothesis testing and interaction effects were analysed using Moderated Regression Analysis (MRA) via IBM SPSS. Findings - The findings reveal that Work-Life Balance significantly decreases Turnover Intention. This relationship is reinforced by Perceived Organizational Support and attenuated by Perceived Job Opportunities. Research Limitations - Practically, management must provide flexible scheduling, fair workloads, and clear internal career paths to counter external job offers. Theoretically, this study extends social exchange and job mobility theories by linking internal organisational support with external labour market alternatives. However, the scope remains limited to the coffee retail sector within a single metropolitan city. Originality - This study offers a distinct contribution by simultaneously integrating internal support mechanisms (POS) and external market pull factors (PJO) as moderators. While prior studies evaluate these elements in isolation, this research provides a comprehensive, holistic framework capturing the unique career behaviours and retention dynamics of Generation Z within the rapidly growing modern coffee retail industry in emerging markets.